2023
DOI: 10.3390/molecules28020661
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology: A Revolution in Modern Industry

Abstract: Nanotechnology, contrary to its name, has massively revolutionized industries around the world. This paper predominantly deals with data regarding the applications of nanotechnology in the modernization of several industries. A comprehensive research strategy is adopted to incorporate the latest data driven from major science platforms. Resultantly, a broad-spectrum overview is presented which comprises the diverse applications of nanotechnology in modern industries. This study reveals that nanotechnology is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
144
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 401 publications
(145 citation statements)
references
References 129 publications
0
144
0
1
Order By: Relevance
“…The best feature of this antiviral agent is that it decreases the symptomology to avert lesions formation and reduces mortality rates. It is used as a second-line therapy for severe vaccinia [ 82 , 99 ]. Specifically, in the case of mpox, the trials have demonstrated reversed mpox by inhibiting mpox replication (proven in vitro and in vivo experiments) [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The best feature of this antiviral agent is that it decreases the symptomology to avert lesions formation and reduces mortality rates. It is used as a second-line therapy for severe vaccinia [ 82 , 99 ]. Specifically, in the case of mpox, the trials have demonstrated reversed mpox by inhibiting mpox replication (proven in vitro and in vivo experiments) [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is preferred for rapid and widespread administration in cases of emergency outbreaks. Unlike cidofovir, it has good oral bioavailability and no reported nephrotoxicity; therefore, it is approved for oral administration [ 82 , 83 , 99 ]. However, the liver enzymatic profile must be carefully regulated, and functional tests must be conducted for the application.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Biotechnologically or environmentally produced nanoparticles have several desirable properties, including high stability and size. Many different methods, including chemical, physical, and biological processes, can be used to generate nanoparticles [ 21 , 22 , 23 , 24 , 25 , 26 ]. There is a risk to human and environmental health from the employment of chemicals and physical procedures due to the high levels of radiation, highly specific reductants, and potentially hazardous agents.…”
Section: Introductionmentioning
confidence: 99%